Fabrication and position control of YICAL torso containing a two-dimensional mass damper system - Pateña, Paul Michael M.
The legs are the basic foundation of creating a humanoid robot. Introducing balance to a bipedal robot is difficult due to the location of its center of mass. The primary objective of this research is to develop a humanoid torso containing a mass damper system, capable of moving along two dimensions. More specifically, the intent is to help stabilize the leg and torso system by replicating the human central nervous system response during gait. The torso frame and the damper system will be integrated with the YICAL Leg II and therefore it needs to be lightweight. The mechanical system will be designed, modeled and fabricated to produce a lightweight system. Position and motor control will be performed using the digital signal processor that is primarily used in controlling the biped. The damper system should be able to react fast enough to help in stabilizing the system. The project would be tested by entering the desired position and the mass damper system should move correspondingly. It is expected that this project will prove valuable in helping the biped legs maintain its stability.